Evaluating the implementation of authentic assessments in junior high school English lesson - Retno Sulistio Ningsih; Nur Wahyumiani (Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
This study aims to describe the quality and implementation of authentic assessment planning of English subject at junior high schools in Yogyakarta. This evaluation research used a discrepancy evaluation model. It was conducted at three state junior high schools (Sekolah Menengah Pertama or SMP negeri) in Yogyakarta, which were pilot projects of Curriculum 2013, namely SMP Negeri 5, SMP Negeri 8, and SMP Negeri 15. The data in this study were obtained through documentation, interviews, and questionnaires. The sample was six English teachers of grade VIII and 549 grade VIII students who were taught by the teachers. The data analysis involved descriptive quantitative and qualitative analyses. The results of the study are as follows. First, 50% of the lesson plans made by teachers are in a good category. All (100%) of the lesson plans assess attitude, knowledge, and skill. Some of the lesson plans (33%) include assessment techniques that are in accordance with the competencies assessed, 50% of the lesson plans use high order thinking skill (HOTS) questions, while the other 50% use realistic questions. Second, 51% of the teachers conducted authentic assessments, which are in a good category. Most (77%) of the teachers assessed attitude, knowledge, and skill, 57% of them gave HOTS questions, most (87%) of them gave realistic questions, and most (63%) of them assessed attitude, knowledge, and skill during the learning process.